Statistical tools for alternative research in plant experiments - Brizzi, Maurizio (Metodološki zvezki, 2010)
In this paper we describe the set of statistical tools applied for evaluating a series of experiments concerning the effects of homeopathic treatments in simple plant models, involving wheat seeds and seedlings and tobacco plants. The homeopathic treatment used in our experiments is arsenic trioxide, diluted in a decimal scale and dynamized k times (with k varying from 5 to 45). Since the most significant results have been achieved with As 45dH (45-th decimal potency of As2O3), we report a brief summary of these results. The statistical analysis was performed by using parametric and non parametric tests, and Poisson distribution has an essential role when dealing with germination experiments. Finally, we describe some interesting results related to the changes in variability, which seems to be a primary target of homeopathic treatment effect.
Keywords: Plants; Rastline; therapy; Zdravljenje; Medical treatment; Homeopathy; Homeopatija; Statistical analysis; Statistična analiza